PERAN SIKAP DALAM MEMEDIASI PENGARUH PERCEIVED USEFULNESS TERHADAP NIAT MENGGUNAKAN INTERNET BANKING DI KOTA DENPASAR - Linda Novita, Ni Nyoman Suaryani; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2016)
This study aims to determine how the effects of perceived usefulness and attitude toward one's intention in using internet banking in Denpasar. The location for this reseacrh held in Denpasar. The number of samples taken is 140 people, with a purposive sampling technique and methods used are non-probability sampling. There are two ways in which the data collection was questionnaires and interviews. Path analysis is a technique of analysis in this study, and Sobel test for the role of mediation. This research is to obtain results which stated that the perceived usefulness has a positive influence and significant also partially on a person's intentions and attitudes toward using internet banking in Denpasar. There was a significant positive effect and influence attitudes towards one's intention to use internet banking in Denpasar. Found also the intention to use internet banking in Denpasar can be influenced by perceived usefulness and attitude partially as a mediating variable.
Keywords: perceived usefulness, attitude, intention to use